Inflammation induces stress erythropoiesis through heme-dependent activation of SPI-C - Bennett, Laura F. (Sci Signal, 2019)
Inflammation alters bone marrow hematopoiesis to favor the production of innate immune effector cells at the expense of lymphoid cells and erythrocytes. Furthermore, proinflammatory cytokines inhibit steady-state erythropoiesis, which leads to the development of anemia in diseases with chronic inflammation. Acute anemia or hypoxic stress induces stress erythropoiesis, which generates a wave of new erythrocytes to maintain erythroid homeostasis until steady-state erythropoiesis can resume. Although hypoxia-dependent signaling is a key component of stress erythropoiesis, we found that inflammation also induced stress erythropoiesis in the absence of hypoxia. Using a mouse model of sterile inflammation, we demonstrated that signaling through Toll-like receptors (TLRs) paradoxically increased the phagocytosis of erythrocytes (erythrophagocytosis) by macrophages in the spleen, which enabled expression of the heme-responsive gene encoding the transcription factor SPI-C. Increased amounts of SPI-C coupled with TLR signaling promoted the expression of Gdf15 and Bmp4, both of which encode ligands that initiate the expansion of stress erythroid progenitors (SEPs) in the spleen. Furthermore, despite their inhibition of steady-state erythropoiesis in the bone marrow, the proinflammatory cytokines TNF-α and IL-1β promoted the expansion and differentiation of SEPs in the spleen. These data suggest that inflammatory signals induce stress erythropoiesis to maintain erythroid homeostasis when inflammation inhibits steady-state erythropoiesis.